Encyclopedia of networked and virtual organizations - Putnik, Goran, 1954-; Cruz-Cunha, Maria Manuela, 1964- (Hershey, PA : Information Science Reference, 2008)
"This book documents the most relevant contributions to the introduction of networked, dynamic, agile, and virtual organizational models; definitions; taxonomies; opportunities; and reference models and architectures. It creates a repository of the main developments regarding the virtual organization, compiling definitions, characteristics, comparisons, advantages, practices, enabling technologies, and best practices"--Provided by publisher
v. 1. A - F -- v. 2. G - Pr -- v. 3. Pu - Z
Includes bibliographical references and index
1
Keywords: Business enterprises -- Computer networks; Knowledge management; Management information systems; Virtual corporations; Virtual reality in management